2009
DOI: 10.1038/onc.2009.286
|View full text |Cite
|
Sign up to set email alerts
|

Genetic inactivation of ApoJ/clusterin: effects on prostate tumourigenesis and metastatic spread

Abstract: ApoJ/Clusterin (CLU) is a heterodimeric protein localized in the nucleus, cytoplasm or secretory organelles and involved in cell survival and neoplastic transformation. Its function in human cancer is still highly controversial. In this study, we examined the prostate of mice in which CLU has been genetically inactivated. Surprisingly, we observed transformation of the prostate epithelium in the majority of CLU knockout mice. Either PIN (prostate intraepithelial neoplasia) or differentiated carcinoma was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 37 publications
(43 reference statements)
4
43
0
Order By: Relevance
“…The highly significant inverse correlation found between CLU and Nf-kB expression is consistent with what is already known about the inhibitory activity of CLU on Nf-kB activity and expression [15]. However, although Nf-kB is known to be involved in initiation and cancer progression, there are no studies showing a correlation between Nf-kB and cancer OS and DFS.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The highly significant inverse correlation found between CLU and Nf-kB expression is consistent with what is already known about the inhibitory activity of CLU on Nf-kB activity and expression [15]. However, although Nf-kB is known to be involved in initiation and cancer progression, there are no studies showing a correlation between Nf-kB and cancer OS and DFS.…”
Section: Discussionsupporting
confidence: 75%
“…Several in vitro studies demonstrated that Nf-kB activation is inhibited by CLU [13,14] and that the deletion of CLU induces activation of Nf-kB [15] suggesting an interrelationship between these 2 proteins.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that CLU expression levels correlated positively with most inflammatory diseases and virus infections [16]. More recently, CLU gene expression was found to be induced during progression of primary osteoarthritis [67]. Interestingly, CLU seems to also directly intervene in NF-κB regulation, although its role remains debated; depending on the experimental model, CLU had either a negative [39] or a positive effect [40] on NF-κB activity.…”
Section: Functional Implication Of Clu In Ageing and Age-related Disementioning
confidence: 99%
“…As a tumor modifier, clusterin may interfere with several signaling pathways mediated by NF-κB, PI3 kinase, or MAP kinase [5,15,18]. A few studies have focused on nuclear clusterin, a cell death protein that plays a pro-apoptotic role [11,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…This downregulation may promote tumorigenesis and metastasis. Several recent studies have shown that genetic inactivation of clusterin can promote tumorigenesis and metastasis [14,15]. In addition, clusterin represents a positive biomarker of better overall survival [16,17,18].…”
Section: Discussionmentioning
confidence: 99%